2001
DOI: 10.1088/0034-4885/64/5/201
|View full text |Cite
|
Sign up to set email alerts
|

Surface stress of clean and adsorbate-covered solids

Abstract: Starting with a simple introduction into the phenomenon of surface stress from a thermodynamic as well as from an atomistic viewpoint, the currently available literature on surface stress of clean and adsorbate-covered surfaces is reviewed. The equations which are used to calculate the adsorbate-induced changes of the surface stress tensor from cantilever bending experiments are derived and their limitations are discussed. It is shown for several examples that charge transfer effects have a pronounced influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
370
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(396 citation statements)
references
References 217 publications
(456 reference statements)
22
370
1
3
Order By: Relevance
“…The appearance of more precise measurements from Haines and McIntosh 9 showed that the strain isotherms for microporous materials have a small region where the samples contract, which could not be explained by Bangham's equation (3). The contraction in the beginning of the strain isotherm was further confirmed in several other experimental works 10,77,78 and the following explanation was given by Lakhanpal and Flood.…”
Section: Contraction At Low Pressuresmentioning
confidence: 82%
See 2 more Smart Citations
“…The appearance of more precise measurements from Haines and McIntosh 9 showed that the strain isotherms for microporous materials have a small region where the samples contract, which could not be explained by Bangham's equation (3). The contraction in the beginning of the strain isotherm was further confirmed in several other experimental works 10,77,78 and the following explanation was given by Lakhanpal and Flood.…”
Section: Contraction At Low Pressuresmentioning
confidence: 82%
“…There has been a vast literature on stresses at the plain surfaces induced by gas or electrolyte adsorption, many of which are summarized in a seminal review by Haiss. 3 …”
Section: -9401/2017/4(1)/011303/24mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface stresses, measured by a variety of methods, for metals are usually tensile and relatively large, in the range of 2 N/m. 3,4) These are of course strongly influenced by the details of any surface reconstruction and the adsorption of foreign species, hence whether or not the surface is cleaned to the high standards of ultrahigh vacuum (UHV) conditions. If such a stress is present on the surface of a spherical particle of radius R, the surface stress S will give rise to a pressure difference ÁP between the inside and outside, according to the classical Gibbs-Thomson equation, otherwise known as the Young-Laplace equation, used to explain the stability of soap bubbles among many other applications:…”
Section: Structure Of Nanoparticlesmentioning
confidence: 99%
“…An investigation of the double-layer region [10][11][12][13] (i.e., when no electrochemical reaction occurred) as well as 3 adsorption reactions [14][15][16][17] and electrodeposition [18] have been carried out using the standard optical lever technique [1].…”
mentioning
confidence: 99%